The Washington Redskins : when public perception challenges a brand - Ludwig, Carson; Wallace, Kaitlyn (London : The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame, 2020)
The Washington Redskins professional football team face a new social climate with the sudden rise of power and influence of the Black Lives Matter Movement. The team, its owners, sponsors and fans confront a momentous shift in American tolerance for racially charged brands following the death George Floyd in 2020. Sponsorship arrangements, logotypes, even the team's name are under fire.
Originally Published InLudwig, C. & Wallace, K. (2020). The Washington Redskins: When Public Perception Challenges a Brand. 20-10. Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Washington Redskins (Football team), -- Case studies; Corporations -- Public relations -- Case studies; Corporate image -- Case studies; Branding (Marketing) -- Case studies